Economia e Diritto in Italia durante il Fascismo Approfondimenti, biografie, nuovi percorsi di ricerca - Barucci, Piero; Bini, Piero; Conigliello, Lucilla (Studi e saggi, 2017)
The volume collects eight essays on economic and legal culture in Italy in the period between the two world wars. Some of the essays investigate the relationship between the fascist regime and intellectuals, as in the case of the jurist Alfredo Rocco and the economists Luigi Amoroso, Arrigo Serpieri and Alberto Bertolino. Other essays deal with the ways and places through which economics and law were popularised during the fascist dictatorship. The in-depth cases are those of the Bocconi University of Milan and of the School of Corporate Sciences of Pisa. Finally, two essays deal with economic policy in the liberal phase of fascism and with the nature assumed by the legal debate on the corporate problem, identifying in these experiences salient moments of the evolution of the relationship between state and market.